Meeting the Traditional Marketing Goals through Social Media: Case Study of Asus Corporation - Djallam, Karima; Benhadjouba, Hamid (المركز الجامعي أحمد زبانة غليزان - معهد العلوم الاقتصادية والتجارية وعلوم التسيير, 2018)
The purpose of this paper is to highlight the importance of social media as a new marketing tool that serves the goals of the traditional marketing and helps institutions to improve their marketing performance. In order to meet those goals we decided to study Asus corporation experience in using social media marketing through presenting the initial projects and objectives, strategies and their achievements.
تهدف هذه الورقة البحثية إلى إبراز أهمية وسائل التواصل الاجتماعي كأداة تسويقية جديدة تخدم أهداف التسويق التقليدي وفي نفس الوقت تساعد وتعمل على تحسين الأداء التسويقي للمؤسسات. ومن أجل غاية بحثنا المنشودة قررنا دراسة تجربة شركة Asus"" الناجحة في تطبيق التسويق عبر وسائل التواصل الاجتماعي من خلال استعراض مشاريعهم وأهدافهم الأولية، الاستراتيجيات المتبعة في تطبيق التسويق عبر وسائل التواصل الاجتماعي وأخيراً النتائج والإنجازات المتوصل إليها.
Keywords: السياسة الإقتصادية -- التنمية الإقتصادية -- النمو الإقتصادي -- التنمية المستدامة -- التسويق والترويج -- وسائل الإتصالات -- مواقع التواصل الإجتماعي -- الإنترنت -- الجزائر -- المجتمع الجزائري -- مستخلصات الأبحاث